CONSUMPTION WITH REGARD TO CULTURAL DYNAMICS OF GLOBALISATION - Eker, Hülya (Bursa Teknik Üniversitesi, 2018)
One of the most commonly used terms nowadays is globalization. Considering globalization as a process has a critical role in understanding its economic, cultural, and political effects on society. These effects of globalization can be felt directly or indirectly in every part of the society. One of the most common effects is that many phenomena, consumption itself and consumption habits have become controversial topics in today’s world where human relations have become more mobile than they ever were. Under cultural codes for consumerist individuals, fulfilling needs, as Bauman, Baudrillard, and Bourdieu handle in different aspects, refers to a symbol of power and status as well as an expression of belonging to a particular class. In this regard, this study discusses that fulfilling the need for consumption is a significant phenomenon in determining power, status and belonging to a particular class

Günümüzde en yaygın kullanılan kavramlardan biri küreselleşmedir. Küreselleşmeyi bir süreç olarak görmek toplumdaki ekonomik, kültürel, siyasi etkilerini net görebilmek açısından önem arz etmektedir. Küreselleşmenin etkileri toplumun her alanında doğrudan ya da dolaylı olarak hissedilmektedir. Bunun en açık etkilerinden biri ise insan ilişkilerinin hiç olmadığı kadar akışkan olduğu günümüzde birçok olgu tüketim ve tüketim alışkanlıkları oldukça tartışılan bir kavramdır. Tüketim bireyleri için kültürel kodlar altında Bauman, Baudrillard, Veblen gibi araştırmacıların farklı yönleriyle ele aldıkları haliyle ihtiyacın karşılanması, güç ve statü simgesi, belirli bir sınıfa ait olmanın ifadesi olarak görülmektedir. Bu bağlamda yapılan bu çalışmada tüketim ihtiyacı karşılanması, güç statü, belirli bir sınıfa ait olmayı belirlemede etkili bir olgu olarak tartışılmıştır.
KÜRESELLEŞMENİN KÜLTÜREL DİNAMİKLERİ AÇISINDAN TÜKETİM